Eu(III)-coordination polymer: selective detection of Cu2+ ion and treatment activity on the sepsis in newborns by reducing virulence expression in Staphylococcus aureus. (10th November 2021) - Ouyang, Fulian; Yi, Ling; Wen, Lifang; Qi, Hongliang; Zhou, Qili; Zeng, Shuying
ABSTRACT: A novel coordination polymer (CP) based on Eu(III) ion as node [EuK(BPDSDC)(DMF)(H2 O)2 ]n (1, DMF = N, N-dimethylformamide) was produced via application of the bifunctional carboxylic acid sulphonate ligand of the biphenyl-3, 3′-disulfonyl-4, 4′-dicarboxylate (BPDSDC 4 − ). Furthermore, complex 1 could be applied as a probe for sensing Cu 2+ ion via fluorescence quenching. The coefficient of quenching Ksv was 7.7 × 10 4  M −1, which was one of the highest values recorded for CPs of Cu 2+ sensing in water solutions. To develop novel candidates for the treatment of sepsis in newborns induced by Staphylococcus aureus infection, inhibition of compound against virulence expression in S. aureus was determined by real-time reverse transcription-polymerase chain reaction. Then, inflammatory cytokine content in plasma was measured via the enzyme-linked immunosorbent assay test kit. Excellent inhibitory effect of the compound on the sepsis of newborns was revealed for the first time.